Granulocyte colony-stimulating factor and respiratory status of critically ill neutropenic patients with hematologic malignancies. Issue 5 (16th April 2019) - Mignard, Xavier; Biard, Lucie; Lemiale, Virginie; Mokart, Djamel; Pène, Frédéric; Kouatchet, Achille; Mayaux, Julien; Vincent, François; Nyunga, Martine; Bruneel, Fabrice; Rabbat, Antoine; Lebert, Christine; et al.
Abstract: In patients with hematologic malignancies, respiratory status may deteriorate during neutropenia recovery. This multicenter, observational study aims to evaluate granulocyte colony-stimulating factor (G-CSF) impact on respiratory status in critically ill neutropenic patients. Among 1011 critically ill patients with hematologic malignancies, 288 were neutropenic and included in this study. 201 (70%) did not receive G-CSF at day 1 or 2. After propensity score matching for the probability of receiving G-CSF at day 1 or 2, there was no association between G-CSF and respiratory deterioration at day 14 (OR =1.19; 95%CI (0.57–2.51); p  = .64). Additional sensitivity analysis in patients admitted for acute respiratory failure showed similar results (OR =1.34; 95%CI (0.5–3.59); p  = .57). Among patients who recovered from neutropenia, 75% experienced respiratory deterioration during neutropenia recovery. This study confirms that neutropenia recovery is a situation at risk of respiratory deterioration. However, whether G-CSF is an aggravating factor cannot be supported by our results.